Respostas

2014-06-16T23:10:11-03:00
A-) 3x-x=3-7. -->2x=-4. --> x=-2

b-)3x+2x= 4-4. -->x=0

c-)6x-5x=2-5. -->x=-3

d-)-3x+3x+2x=12-2. -->2x=10. -->x=5

e-)7x+2x+3x-x=8+4. -->11x=12. -->x=12/11 = 1,09
2014-06-16T23:19:40-03:00
Lembre-se multiplicação e divisão primeiro e sempre separe letras de número.
3x+7=x+3
3x-x=-7+3
2x=-4
x=-2

-7x+4+10x=4-2x
3x+4=4-2x
4-4= 3x+2x
0/5=x
x=0
5+6x=5x+2
5-2=5x-6x (-x ou -1x)
x= -3
2-3x= -2x+12-3x
12-2= 5x-3x
10/2=x
x=5
7x-4-x=-2x+8-3x
7x-4=-5x+8
8+4=7x+5x
12=12x
12/12=1